Geopolitical Analysis of government Expenditure on Scientific Research: Turkey and Saudi Arabia as examples - Mahdi, basim hameed; muheemed, katab saad (Journal of Tikrit University for Humanities, 2024)
The development of government spending on scientific research has witnessed significant growth during the period (2018-2022). This growth has reflected positively on the nation’s status and economic strength. Both Turkey and Saudi Arabia have allocated funds to develop their economic structure by diversifying the economic base and promoting the development process, as indicated by economic indicators. Research and development is a crucial indicator for measuring a country’s progress and is a key investment pillar that contributes to gaining sustainable competitive advantages and adapting to environmental changes. Through technological advancement, an economy can grow steadily and continuously, even without changes in the quantities of other production factors, by improving efficiency and increasing the productivity of production factors. Various measures and policies aim to diversify the economic structure to achieve geopolitical objectives. The study relied on analyzing economic indicators of each country and their contribution to the development and increase of economic growth, enabling them to face challenges and difficulties in the region, particularly in the era of technological advancements that the world is witnessing, thereby enhancing their economic and political status in the regional and international arenas.